Numerical investigation of tangent hyperbolic nanofluid with stagnation point flow of irregular heat and Darcy-Forchheimer effects on stretching sheet - Srinivas Reddy Kallem; Siva Reddy Sheri; Alfunsa Prathiba Perli; Medhat M. Helal; AI Ismail (Results in Engineering, 2025)
This study presents a numerical analysis of magnetohydrodynamic (MHD) stagnation point flow of a hyperbolic tangent nanofluid (HTNF) over a linearly stretching surface, incorporating the effects of nonlinear heat generation/absorption, chemical reactions, and porous media resistance modeled by the Darcy–Forchheimer relation. The hyperbolic tangent fluid model, a key representative of non-Newtonian fluids, is employed due to its enhanced thermal conductivity under varying shear rates, making it suitable for advanced heat and mass transfer applications. Governing partial differential equations, derived from conservation laws and appropriate boundary conditions, are reduced to a system of nonlinear ordinary differential equations using similarity transformations. The resulting system is solved numerically via MATLAB's built-in bvp4c solver. A detailed parametric study is carried out to examine the effects of velocity ratio (λ), space- and temperature-dependent heat source/sink parameters (A, B), magnetic field intensity, Brownian motion, thermophoresis, chemical reaction rate, and porous medium properties on velocity, temperature, and concentration distributions. Key performance indicators including the skin friction coefficient, local Nusselt number, and Sherwood number are computed and analyzed to assess thermophysical behavior. Results reveal that increasing the chemical reaction rate enhances mass transfer by lowering nanofluid concentration, while higher stretching parameters suppress flow velocity and increase thermal and solutal boundary layers. The model generalizes flow over both linear and nonlinear stretching surfaces (n = 1 for linear), making it versatile for industrial applications. This work offers valuable insights for improving thermal regulation in MHD power systems, nuclear reactor cooling, aerospace thermal protection, and magnetically guided drug delivery.